KARAKTERISTIK KARAGENAN DARI RUMPUT LAUT E. Spinosum DENGAN PERLAKUAN KONSENTRASI NaOH DAN LAMA WAKTU EKSTRAKSI YANG BERBEDA - Umbu, Krisman; Nasution, Nur Azizah; Banju, Yudianto Nggaba Hamba (Jurnal Perikanan Unram, 2024)
Carrageenan has benefits in the fields of food, cosmetics and medicine. Carrageenan extraction generally uses chemicals as a catalyst, for example potassium hydroxide (KOH). However, on the other hand, there are several other alkaline compounds such as sodium hydroxide (NaOH) that can be utilized. Apart from that, the effect of extraction time also greatly influences the characteristics of the carrageenan produced. The research results show the characteristics of carrageenan produced from E. Spinosum seaweed, namely the yield ranges from 22.49% - 37.58%, water content 09.33% - 14.32% and viscosity 38.23 cPs - 51.33 cPs. The characteristics of this carrageenan generally meet the commercial standards for carrageenan. The treatment of NaOH concentration and extraction time had a real influence on the yield, water content and viscosity of the resulting carrageenan.